LED TV IN THE CLASSROOM: IT’S ACCEPTABILITY AND EFFECTIVENESS IN THE PHILIPPINES - Averion, Rebecca F; Caleja, Heidi Belle F; Zapanta, Victoria M (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study intends to surface the effects of using LED TV in the classroom utilizing a mixed method of quantitative to analyze teachers’ acceptability; and qualitative through phenomenology to describe the essence of the live-experienced of teachers; and phenomenography to structure the effect of LED TV in the learning of the students. Through validated researcher acceptability survey questionnaire, semi-structured interview guide, focus group discussion anchored in the Unified Theory of Acceptance and Use of Technology and Technology Acceptances Model (Kolog et al., 2015), and the richness of the data gathered, this study surfaced that the use of LED TV in the classroom is an effective and useful educational-technological tool, for it creates various effects both to teachers and students. With the use of LED TV, teachers became competent, confident, and effective teachers.